Liver and Renal Cell Damage Following Excess Bee Honey Consumption in Male Wistar Rat - Akpevwoghene Agbatutu; Jerome Ndudi Asiwe; Olusegun Gafar Adebayo (Biology, Medicine, & Natural Product Chemistry, 2022)
Honey is a widely used natural product with several health benefits. However, there is paucity of information on its excessive usage. The present study investigated the effect of excess honey consumption on hepato-renal functions in male wistar rats. Twenty-eight adult male Wistar rats were selected into four groups (n=7) and treated with distilled water (control) and 1ml, 2ml and 3ml of honey respectively for 5 weeks. Thereafter, the animals were euthanised and blood as well as kidney and liver were collected for further studies. There was a significant increase in Creatinine, Bilirubin, Urea AST, ALP, total protein as well as a significant decrease in RBC, WBC, haemoglobin, lymphocyte and PCV. Histology of the liver and kidney revealed a significant degeneration and necrosis in a dose dependent manner. This study suggest that excess honey consumption causes liver and renal cellular damage as well as haematological alterations.